Pengampuan Atas Istri yang Mengalami Dimensia dalam Penjualan Harta Bersama - Cynthia Nugroho; Suraji Suraji (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
Ownership of assets in marriage is divided into 2 (two) things, namely joint assets and inherited assets. Regarding joint assets, the sale must be with the consent of the husband and wife. Sales as an agreement require that both parties are legally competent. This research examines the sale of joint property if the wife is in a state of incompetence, namely experiencing dementia. This research is normative legal research with a conceptual approach and a statutory approach. It was concluded that wives who were incompetent due to dementia had to be represented by other. To facilitate the buying and selling process, curatele can be given to the children of the husband and wife.